"It's the single best thing I've done in the last 10 years": a qualitative study exploring patient and dietitian experiences with, and perceptions of, a multi-component dietary weight loss program for knee osteoarthritis. Issue 4 (April 2021) - Lawford, B.J.; Bennell, K.L.; Jones, S.E.; Keating, C.; Brown, C.; Hinman, R.S.
Summary: Objective: Explore patient and dietitian experiences with a multi-component dietary weight loss program for knee osteoarthritis to understand enablers and challenges to success at 6-months. Design: Qualitative study embedded within a randomised controlled trial. Semi-structured individual interviews with 24 patients with knee osteoarthritis who undertook, and five dietitians who supervised, a weight management program (involving a ketogenic very low calorie diet (VLCD), video consultations, educational resources) over 6 months. Data were thematically analysed. Results: Five themes were developed: (1) ease and convenience of program facilitated adherence (structure and simplicity of the meal replacements; not feeling hungry on diet; convenience of consulting via video) (2) social and professional support crucial for success (encouragement from partner, family, and friends; guidance from, and accountability to, dietitian; anxiety around going at it alone) (3) program was engaging and motivating (determination to stick to program; rapid weight loss helped motivation) (4) holistic nature of program was important (suite of high-quality educational resources; exercise important to compliment weight loss) (5) rewarding experience and lifelong impact (improved knee pain and function; positive lifestyle change). Conclusions: Patients and dietitians described positive experiences with the weight management program, valuing its simplicity, effectiveness, and convenience. Support from dietitians and a comprehensive suite of educational resources, incorporated with an exercise program, were considered crucial for success. Findings suggest this multi-component dietary program is an acceptable weight loss method in people with knee osteoarthritis that may benefit symptoms. Strategies for supporting long-term independent weight management should be a focus of future research.